Conservative treatment of odontogenic fibromyxoma in the mandible: report of two cases - Conto-Palomino, Jackeline Paola (2023)
Introduction: Odontogenic fibromyxoma is a rare benign tumor of mesenchymal origin. Small tumors may be asymptomatic and are discovered only during the routine radiographic examination, and large tumors are associated with the painless expansion of bone with the displacement of teeth and bone perforation. The treatment option is surgical and can range from conservative treatment to radical excision. Case Report: We report two cases of fibromyxoma in the mandible in a 17-year-old woman and an 18-year-old man. The diagnosis was anatomopathological. Both underwent conservative enucleation treatment with peripheral osteotomy and extraction of the affected teeth with favorable evolution. Discussion: Conservative treatment with an intraoral approach is a humanistic alternative that maintains its value of success, favorable evolution, and great acceptance by patients.